Not everything is as the eyes see: the role of physical-sensory elements and self-confidence in the vulnerability of consumers with visual impairment - Lucena Filho, Rômulo Benício; Aguiar, Edvan Cruz (Revista de Administração da UFSM, 2024)
Objectives: This study aims to analyze how physical-sensory elements of the retail environment and self-confidence relate to the perceived vulnerability of visually impaired consumers and their shopping experience. It seeks to demonstrate how factors such as store layout, the need for tactile interaction, and self-confidence influence perceived vulnerability and satisfaction among visually impaired consumers during the shopping experience. Method/approach: The study adopts a descriptive quantitative approach, using a questionnaire-based research method to collect data from318 visually impaired individuals in the state of Paraíba, Brazil. The questionnaire includes measurement scales for various constructs related to the retail environment and consumer behavior, as well as demographic questions to characterize the sample. Results: The results reveal significant relationships between store layout, tactile need, self-confidence, perceived vulnerability, and satisfaction among visually impaired consumers. Specifically, store layout and self-confidence were found to have negative associations with perceived vulnerability, while tactile need had a positive association. Perceived vulnerability, in turn, had a negative association with satisfaction. Limitations/research implications: The study acknowledges limitations such as sample size and geographic specificity, suggesting the need for further research to validate the results in different contexts and populations. Theoretical implications include the need for a deeper understanding of consumer vulnerability and its impact on retail experiences. Practical implications: The study highlights the importance of accessible store design and customer service training to improve the shopping experience of visually impaired consumers. It also underscores the potential benefits of addressing the tactile needs of these consumers. Social implications: By promoting social inclusion and accessibility in retail environments, the study contributes to a more equitable shopping experience for individuals with visual impairments, fostering social inclusion and equality. Originality/value: This study contributes to the limited literature on the retail experiences of consumers with visual impairments, offering insights into the factors influencing their perceived vulnerability and satisfaction. It emphasizes the importance of considering the unique needs of this consumer segment in retail design and service provision.